Multifunctional non-woven fabrics of interfused graphene fibres - Zheng Li (Nature Portfolio, 2016)
Carbon-based fibres are at the core of electrically conductive multifunctional fabrics, yet improving the weak interaction between fibres remains a challenge. Here, the authors demonstrate an assembly method where graphene fibres are fused at junctions with record specific electrical and thermal conductivity.